Study of a novel inlet geometry for ejectors. (July 2022) - Bauzvand, Amin; Tavousi, Ebrahim; Noghrehabadi, Aminreza; Behbahani-Nejad, Morteza
Highlights: New geometries of ejector can improve the performance of ejector. The multi-nozzle extends shear layer and swirls effect makes faster and laterally distributed mixing process. By decreasing the mixing process, the ejector needs a shorter mixing length. The efficiency of the ejector with new geometry increased up to 158% rather than the conventional geometry. Abstract: Enhancing the ejector's performance increases the ejector refrigeration systems' performance and increases their competitiveness in real applications. In this paper, a new concept for ejector geometry, different from conventional geometry, has been proposed to improve their performance characteristics and dimensional compactness for small scale applications like household air conditioning. The proposed inlet geometry has the multi-nozzle and swirls effect features simultaneously. The proposed geometry has been applied to a liquid-gas two-phase ejector in this study. Then, the liquid-gas two-phase flow inside the ejector was studied by CFD, and experiments validated the performance results. The velocity and pressure fields have been studied in different operating conditions. The obtained results show that pressure, velocity, and the phases' volume fractions change oscillating with gradually damping amplitude along with the ejector axis, which means there is no sensible mixing shock in the mixing process. The mixing process completes in a relatively short distance and the required mixing section length becomes less. Also, the results of the proposed ejector were compared with the experimental results of a conventional ejector. The results show that the new ejector has a better entrainment ratio and efficiency than the conventional ejector in similar operating conditions. The maximum enhancement of efficiency of the new geometry occurs at 116.67 lit min-1 primary flow volume rate, and it is 158% higher than the conventional geometry.